Father Payne - Benson, Arthur Christopher, 1862-1925 (Salt Lake City, UT : Project Gutenberg, 2004)
"Father Payne" by Arthur Christopher Benson is a reflective narrative that likely belongs to the genre of literary memoir or character study, written during the early 20th century. The book centers around the life and philosophy of "Father Payne," a distinctive figure revered by those who knew him, particularly the author. The story unfolds during a time when the social and artistic fabric of Europe was undergoing considerable change, providing a backdrop for discussions on literature, life, and human values. The opening of the book introduces us to the narrator, who recounts his fond memories and admiration for Father Payne, an insightful and unconventional man he encountered in his youthful quest for purpose following his studies at Oxford. In a casual yet intimate setting, we learn about Father Payne's approach to teaching and life$1 (Bemphasizing ideas over rigid structures, independence, and a disdain for conventionality, as he gathers a small community of aspiring writers around him. The narrative hints at the dynamic between Father Payne and his mentee, capturing the essence of Father Payne$1 (Bs wisdom, warmth, and the intellectual freedom he inspires in his followers. The beginning sets the stage for exploring deeper philosophical themes and the transformative influence of mentorship against the quaint backdrop of English rural life. (This is an automatically generated summary.)s
Release date is 2004-05-01
Produced by David Newman and PG Distributed Proofreaders. Produced from images provided by the Million Book Project
Keywords: Philosophy; Ethics; Life